2019
DOI: 10.1039/c8ob02715c
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the vicinal disubstituent effect on the diastereoselective synthesis of γ and δ lactones

Abstract: Trifluoroacetic acid catalysed lactonization of vicinal disubstituted γ-hydroxyesters was investigated in different solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Recently, we studied the acid-catalysed cyclization of a series of alkyl substituted γ- and δ-hydroxy esters and we found that the cyclization rate depends on the relative stereochemistry of the vic -disubstituted precursors ( vic -disubstituent effect), regardless of the catalyst, the leaving group and the solvent used. 8 More precisely, in the case of γ-hydroxy esters, the syn dimethyl substituted diastereoisomer showed a kinetic behaviour quite similar to its gem -dimethyl constitutional isomer, whereas, the anti diastereoisomer ring-closed to the trans lactone almost 20 times faster; analogously, even for the δ-hydroxy esters a vic -disubstituent effect was observed (Fig. 1C).…”
mentioning
confidence: 73%
“…Recently, we studied the acid-catalysed cyclization of a series of alkyl substituted γ- and δ-hydroxy esters and we found that the cyclization rate depends on the relative stereochemistry of the vic -disubstituted precursors ( vic -disubstituent effect), regardless of the catalyst, the leaving group and the solvent used. 8 More precisely, in the case of γ-hydroxy esters, the syn dimethyl substituted diastereoisomer showed a kinetic behaviour quite similar to its gem -dimethyl constitutional isomer, whereas, the anti diastereoisomer ring-closed to the trans lactone almost 20 times faster; analogously, even for the δ-hydroxy esters a vic -disubstituent effect was observed (Fig. 1C).…”
mentioning
confidence: 73%
“…In fact, the cyclization reaction of substituted 4‐aminobutyric acids and 4‐hydroxybutyic acids has been investigated, and increase of cyclization rate by substitution has been confirmed. [ 37–43 ] To this end, we propose to introduce a methyl group into the α ‐position of the ester bond of poly(4‐hydroxybutyric acid) derivative (Scheme 1). Furthermore, to realize the trigger‐induced self‐immolative property, we anchored a silyl ether group to the polymer chain end.…”
Section: Introductionmentioning
confidence: 99%